Comparative Impact of Covid-19 and the Russia-Ukraine War on Global Staple Food Prices - Agus Dwi Nugroho; Zoltan Lakner (Statistika: Statistics and Economy Journal)
This study compares the impact of Covid-19 and the Russia-Ukraine war on global staple food prices to know which is more dangerous. The error correction model (ECM) was used to examine the impact of Covid-19 and the Russia-Ukraine war on global wheat, maize, soybean, and rice prices. The study used data from January 1997–June 2023 from various source databases. Covid-19 increased the global wheat, maize, and soybean prices in the long-run but had no impact at all in the short-run. Meanwhile, the Russia-Ukraine war only raised global wheat prices in the short-run but did not affect other global staple food prices. Covid-19 has spurred a bigger increase in global staple food prices than the Russia-Ukraine war. Increases in the short – and long-run global wheat, maize, and soybeans prices have also been attributed to rising global oil prices. The rise in urea fertilizer prices led to a short- and long-run increase in the price of rice globally while simultaneously lowering the price of wheat globally.